Hackberry Nipplegall Maker (Psyllids) - Brooks, Leroy H. (My University, 2002)
Publication describes hackberry nipplegall maker insects also known as psyllids, for homeowners with hackberry trees.
MF957_2002_09
Keywords: MF957; Insects; MF